POTENSI FAUNA AKUATIK EKOSISTEM HUTAN MANGROVE DI KAWASAN TELUK PANGPANG KABUPATEN BANYUWANGI - Rustrianto Buwono, Yanuar; Ardhana, I.P.G; Sudarma, Made (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2015)
Mangrove ecosystem located between terrestrial and marine coastal areas are changing constantly due to human activities that affect the aquatic fauna several species of fish and non-fish. The aim of research to determine the level of importance and biodiversity index value of mangrove, analyze abundance, biomass, diversity and equity, as well as the spread of aquatic fauna mangrove forest ecosystem. Results of the study showed an index of biodiversity of mangrove flora in the medium category with a relative importance value index Rhizophoraceae and Sonneratiaceae dominate in all phases. Economically valuable aquatic fauna found amounted to 21 species of 15 families. Groups of fish fauna found bedu l fish ( A. caninus ) have abundance and biomass as much as 975 ind at 18,299.56 gr, meanwhile the non fish fauna found werus shrimp ( Metapenaeus sp. ) has an abundance of as much as 1,936 ind and biomass crabs ( P. pelagicus ) have amounted to 13,609.38 gr associated in mangrove areas Pangpang Bay. Fauna biodiversity index included in the medium category, meanwhile the index of evenness fauna belonging in the high category. Dispersal patterns at the mouth of the bay with the mouth of the river flow Wagut fauna found in the form of pelagic and demersal fish such as family Mugilidae, Clupediae, Leiognatidae, Psettodidae . At the center of the edge of the bay in the form of aquaculture ponds found that pelagic fish group Centropomidae , Polynemidae , Sillagidae family. Meanwhile, at the end of the bay with the river flow Setail found the group that demersal fish Platycephalidae and Gobidae family.
Keywords: Biodiversity; Mangrove flora; Fauna; Biomass